2015
DOI: 10.1007/s00192-015-2690-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and predictors of urinary/anal incontinence after vaginal delivery: prospective study of Nigerian women

Abstract: Urinary and anal incontinence are common after vaginal delivery in Enugu, Nigeria. Modification of obstetric care and discouraging preventable predisposing factors for incontinence, such as prolonged second stage of labor and vaginal delivery of macrosomic babies, are measures that may reduce the prevalence of postpartum incontinence in our population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
1
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(69 citation statements)
references
References 26 publications
6
54
1
8
Order By: Relevance
“…No doubt, episiotomy can extend to involve the anal sphincter or decrease the integrity of the perineum, thereby predisposing the clients to fecal and or flatus incontinence . The observed incidence of UI, AI and their distributions at various post‐partum periods are similar to that of a recent study from the study area …”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…No doubt, episiotomy can extend to involve the anal sphincter or decrease the integrity of the perineum, thereby predisposing the clients to fecal and or flatus incontinence . The observed incidence of UI, AI and their distributions at various post‐partum periods are similar to that of a recent study from the study area …”
Section: Discussionsupporting
confidence: 82%
“… On the other hand, data concerning the development of AI were obtained using a pretested questionnaire (Appendix S2). Operational definitions of UI and AI were as described in recently published studies . The cumulative incidence rate of UI was defined as the proportion of women who ever reported any type of UI during the 3‐month follow up and cumulative AI as the proportion of women who ever reported any type of AI during the 3‐month follow up …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies evaluating the relationship between these two variables were not found. However, the literature shows that fetal weight greater than 4 kg is a predictor for urinary and fecal incontinence, suggesting that to prevent such problems, normal birth of macrosomic babies should be avoided 25 .…”
Section: Discussionmentioning
confidence: 99%